2018
DOI: 10.1111/rda.13384
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse (ARFI) elastography to asses maternal and foetal structures in pregnant ewes

Abstract: Contents The aim of this study was to evaluate the stiffness of foetal lungs, liver, kidneys and placentomes by acoustic radiation force impulse (ARFI) elastography in ovine and to correlate obtained findings with foetal development. Twenty‐four ewes were included, and tissue stiffness of foetal lung, liver, kidney and placentome was measured beginning with 10th gestational week by qualitative–quantitative ARFI elastography. A total of 33 healthy lambs were born. Qualitative elastographic analysis permitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…These results are consistent with the findings of Da Silva et al in ovine foetuses, where SWS in the liver gradually increased during gestation [ 25 ]. The use of 2D-SWE in foetal medicine is actually not recommended in current practice, and no health agency has published recommendations about the widespread use of 2D-SWE in obstetrics due to a lack of data concerning the impact of acoustic radiation force on particular displacement in foetal tissues [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the findings of Da Silva et al in ovine foetuses, where SWS in the liver gradually increased during gestation [ 25 ]. The use of 2D-SWE in foetal medicine is actually not recommended in current practice, and no health agency has published recommendations about the widespread use of 2D-SWE in obstetrics due to a lack of data concerning the impact of acoustic radiation force on particular displacement in foetal tissues [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The simultaneous interpretation of the measurement dispersion and elasticity value is interesting because it could reflect histological modifications of both tissues during gestation. For foetal lungs, the development of stiff structures such as blood vessels and bronchi during the canalicular (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and saccular stages (24 WG-term) precedes that of the soft pulmonary parenchyma, especially before 32 WG. During the exploration of the foetal lung with 2D-SWE, the distribution of vasculo-bronchial elements and parenchyma in the same ROI could influence the elasticity measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, research is reported on the fetomaternal elastographic evaluation of dogs, sheep, and baboons. [11][12][13] A limited number of human studies include healthy pregnancies, pregnancies with hypertensive disorders, and fetal abnormalities, investigating the elasticity of the placenta, fetal lungs, liver, brain, and myocardium. [14][15][16][17][18][19][20] As far as we know, our study is the first elastography research on both healthy pregnancies and pregnancies with chromosomal abnormalities including placenta, maternal myometrium, and tissues used in the genetic sonogram.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, research is reported on the fetomaternal elastographic evaluation of dogs, sheep, and baboons 11–13 . A limited number of human studies include healthy pregnancies, pregnancies with hypertensive disorders, and fetal abnormalities, investigating the elasticity of the placenta, fetal lungs, liver, brain, and myocardium 14–20 .…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed during the months of September and November of 2016. Twenty adult multiparous healthy Santa Ines ewes, aged 3.1±1.1 years, weighing 45.4±4.3 kg (before conceiving) and exhibiting a mean body score of 3 (scale 1-5,) ( Jefferies, 1961 ), were selected for this study after checking non-intercurrent full-term normal delivery (singleton gestation only), and normality at physical examination, complete blood count, plasma concentrations of total proteins and fibrinogen, and ultrasonography of the reproductive system ( Silva et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%